2018
DOI: 10.1155/2018/5046372
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum Susceptibility to Neonatal Asphyxia: Possible Protective Effects of N-Acetylcysteine Amide

Abstract: Background After perinatal asphyxia, the cerebellum presents more damage than previously suggested. Objectives To explore if the antioxidant N-acetylcysteine amide (NACA) could reduce cerebellar injury after hypoxia-reoxygenation in a neonatal pig model. Methods Twenty-four newborn pigs in two intervention groups were exposed to 8% oxygen and hypercapnia, until base excess fell to −20 mmol/l or the mean arterial blood pressure declined to <20 mmHg. After hypoxia, they received either NACA (NACA group, n = 12) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Lee et al, (2001) [ 9 ], demonstrated that, in chick embryos, chronic hypoxia (from ED2 to ED21) hinders the normal development of Purkinje cells marked by small cell size, poorly developed dendrites, low cell density, and ectopia. Similar findings were reported in the developing mammalian cerebellum [ 4 , 33 , 34 ]. Biran et al, (2011) [ 4 ], described a decrease in the number of Purkinje cells, granular neurons, and interneurons as well as in the thickness of molecular (ML) and granular (GL) layers in two-day-old rat pups exposed to global hypoxia or hypoxic-ischemia injury.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lee et al, (2001) [ 9 ], demonstrated that, in chick embryos, chronic hypoxia (from ED2 to ED21) hinders the normal development of Purkinje cells marked by small cell size, poorly developed dendrites, low cell density, and ectopia. Similar findings were reported in the developing mammalian cerebellum [ 4 , 33 , 34 ]. Biran et al, (2011) [ 4 ], described a decrease in the number of Purkinje cells, granular neurons, and interneurons as well as in the thickness of molecular (ML) and granular (GL) layers in two-day-old rat pups exposed to global hypoxia or hypoxic-ischemia injury.…”
Section: Discussionsupporting
confidence: 89%
“…The high susceptibility of Purkinje cells to hypoxia may be associated with their high metabolic demand and elaborated synaptic interactions [ 34 ]. The ectopic distribution of Purkinje cells has been reported in some mutant mice with cerebellar abnormalities, e.g., reel mice [ 33 ] and normal rodents [ 35 ]. Thus, our results support the notion that hypoxia disturbs the migration of Purkinje cells on their way to the cerebellar cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Progress has been made in sustaining cerebellar cultures from GA62 fetal guinea pigs using a slightly modified protocol. This brain region is chosen for its high affinity for damage following perinatal insult (Kwan et al, 2015 ; Benterud et al, 2018 ). We further suggest that this protocol could further be adapted to establish cultures from other brain regions such as the hippocampus, further decreasing tissue wastage and improving the relevance of this protocol for investigating perinatal insults that often affect these areas.…”
Section: Discussionmentioning
confidence: 99%